Analisis Pengaruh Kepemimpinan dan Komunikasi Terhadap Motivasi dan Kinerja Pegawai (Satuan Polisi Pamong Praja Kota Surabaya) - Rodhiyallah, Muhammad; Kusmaningtyas, Amiartuti; Tjahjono, Hendro (UNUSA Press, 2017)
The aim of the study was to analyze and determine the influence of leadership and communication, on employee motivation and performance at Satuan Polisi Pamong Praja Kota Surabaya. Branch, as many as 100 persons. Sampling technique samples (Slovin) data was analyzed with multiple linear regression with SPSS for windows program. The result of the research indicated that leadership, communication, and motivation simultaneously have significant effect on employees’ performances with determination value of 0,424 or 4,24%. Leadership, communication and motivation partially has significant effect on performance. Communication itself has dominant effect on employee’s performance.